2020
DOI: 10.1119/1.5145518
|View full text |Cite
|
Sign up to set email alerts
|

Why Are There So Few Women in Physics? Reflections on the Experiences of Two Women

Abstract: Some of the reasons for the underrepresentation of women in physics are evident in the reflections of two undergraduate women. Leia is a chemistry major who loves college-level physical chemistry and quantum mechanics but does not identify with the discipline of physics, partly because she has a low level of self-efficacy as a physicist and has received very little recognition for her work and learning in physics. Paulette is a physics major who loves physics but feels isolated by the current physics learning … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Introduction: Physics has historically been portrayed as a field for brilliant men. Many prior studies have focused on the reasons for women's underrepresentation in physics and related disciplines from different perspectives and strategies to improve the learning environments so that all students can excel in physics courses [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Due to societal stereotypes, women often have significantly lower physics self-efficacy than men even when they perform similarly and many shy away from physics related majors and careers [5,6,9,13].…”
mentioning
confidence: 99%
“…Introduction: Physics has historically been portrayed as a field for brilliant men. Many prior studies have focused on the reasons for women's underrepresentation in physics and related disciplines from different perspectives and strategies to improve the learning environments so that all students can excel in physics courses [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Due to societal stereotypes, women often have significantly lower physics self-efficacy than men even when they perform similarly and many shy away from physics related majors and careers [5,6,9,13].…”
mentioning
confidence: 99%
“…Meanwhile, on the other side of the table, Dan and Cindy's interaction typifies some patterns of gendered interaction in physics, including men getting more attention and more access to equipment [14], [15], [18], [31]- [33]. For example, Dan's possession of the mouse makes the mouse initially inaccessible to Cindy.…”
Section: Critical Perspectivementioning
confidence: 99%
“…It is through student interviews that we uncover a contextual understanding of how women experience and navigate the physics culture. Previous studies that utilize student interviews revealed that women in physics and astronomy experience hostile environments within physics departments [29,30]. In this study, we interview three undergraduate women who are physics majors.…”
Section: Introduction and Frameworkmentioning
confidence: 99%